2020
DOI: 10.1097/01.aoa.0000719608.24257.dc
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose Aspirin for the Prevention of Preterm Delivery in Nulliparous Women With a Singleton Pregnancy (ASPIRIN): A Randomized, Double-blind, Placebo-controlled Trial

Abstract: (Lancet. 2020;395:285–293) Preterm birth is a common cause of infant morbidity and mortality, especially in low- and middle-income countries with limited resources. Previous studies of aspirin used to prevent preeclampsia also suggested that low-dose aspirin may help lower the incidence of preterm births. However, no large-scale trial has specifically evaluated the use of low-dose aspirin initiated in early pregnancy with the primary purpose of preventing preterm birth. The aim of this study (the ASP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a study by Hoffman et al on pregnant women from low- to middle-income countries, low-dose aspiring showed reduced PTD prior to 37 weeks, in addition to decreased perinatal mortality. 25 In contrast, in a study published in 2022 encompassing 608 pregnant women with a history of spontaneous preterm birth, low-dose aspiring did not demonstrate a significant reduction in preterm birth. 26…”
Section: Discussionmentioning
confidence: 90%
“…In a study by Hoffman et al on pregnant women from low- to middle-income countries, low-dose aspiring showed reduced PTD prior to 37 weeks, in addition to decreased perinatal mortality. 25 In contrast, in a study published in 2022 encompassing 608 pregnant women with a history of spontaneous preterm birth, low-dose aspiring did not demonstrate a significant reduction in preterm birth. 26…”
Section: Discussionmentioning
confidence: 90%
“…There may be multiple contributors to the racial disparities in cesarean delivery and pregnancy-associated hypertension that are unrelated to racial differences in labor induction. For example, clinician biases and resource constraints may be associated with suboptimal use of low-dose aspirin for the prevention 26 of pregnancy-associated hypertension.…”
Section: Discussionmentioning
confidence: 99%